Human Oral Epithelial Cells Suppress T Cell Function via Prostaglandin E2 Secretion - Sanchez-Trincado, Jose L.; Pelaez-Prestel, Hector F.; Lafuente, Esther M.; Reche, Pedro A. (Frontiers in Immunology, 2022)
The oral mucosa is constantly exposed to a plethora of stimuli including food antigens, commensal microbiota and pathogens, requiring distinct immune responses. We previously reported that human oral epithelial cells (OECs) suppress immune responses to bacteria, using H413 and TR146 OEC lines and primary OECs in co-culture with dendritic cells (DCs) and T cells (OEC-conditioned cells). OECs reduced DCs expression of CD80/CD86 and IL-12/TNF release and impaired T cell activation. Here, we further evaluated the immunosuppression by these OECs and investigated the underlying mechanisms. OEC-conditioned DCs did not induce CD4 T cell polarization towards Treg, judging by the absence of FoxP3 expression. OECs also repressed T-bet/IFNγ expression in CD4 and CD8 T cells activated by DCs or anti-CD3/CD28 antibodies. This inhibition depended on OEC:T cell ratio and IFNγ repression occurred at the transcriptional level. Time-lapse experiments showed that OECs inhibited early steps of T cell activation, consistent with OECs inability to suppress T cells stimulated with PMA/ionomycin. Blocking CD40/CD40L, CD58/CD2 and PD-L1/PD-1 interactions with specific antibodies did not disrupt T cell suppression by OECs. However, preventing prostaglandin E2 (PGE2) synthesis or blocking PGE2 binding to the cognate EP2/EP4 receptors, restored IFNγ and TNFα production in OEC-conditioned T cells. Finally, treating OECs with poly(I:C), which simulates viral infections, limited T cell suppression. Overall, these results point to an inherent ability of OECs to suppress immune responses, which can nonetheless be eluded when OECs are under direct assault.